JomRonda : Mobile Application for Security Guard Patrolling - binti Bibit, Nur’Ain Syafiqah; binti Abdullah, Zamlina; binti Mior Dahlan, Nurazian; binti Dahlan, Azlin (Information Management and Business Review, 2024)
Security patrolling is the process of routinely walking or driving through an area to maintain safety and follow the rules. Few studies discovered issues in security, accuracy and dependability of using non-computerized devices such as watchman clock. One of the issues is hard to monitor the tasks where the watchman tends to avoid their duties by attempting to use the duplicity and adjustment to the watchman’s clock and the key. Yet, the watchman forgets to make daily reports in a logbook at each checkpoint resulting in inaccuracy for authorities to attend and managing any serious emergency. Focussing on the issues, this application is designed with patrolling techniques called geofencing whereby the watchman’s location is tracked and data about patrolling is recorded to a database once crosses a virtual boundary. Stakeholders get benefit from the application by keeping track of and reading daily reports digitally. Furthermore, it contains SOS features or international standards for signalling distress allowing users to alert one another in the event of an emergency in the area via a form and an in-app notification. This project follows a methodology known as the Modified Waterfall Model, which entails four stages: requirement gathering and analysis, design, implementation and testing. Future improvements are daily and monthly reporting to authorities can be generated and sent through email. Yet, the application needs temporary storage and the database will be updated as soon as the internet connection is restored.